Variance and interest rate risk in unit-linked insurance policies - David Ba\~nos; Marc Lagunas-Merino; Salvador Ortiz-Latorre (Risks, 2020)
One of the risks derived from selling long-term policies that any insurance company has arises from interest rates. In this paper, we consider a general class of stochastic volatility models written in forward variance form. We also deal with stochastic interest rates to obtain the risk-free price for unit-linked life insurance contracts, as well as providing a perfect hedging strategy by completing the market. We conclude with a simulation experiment, where we price unit-linked policies using Norwegian mortality rates. In addition, we compare prices for the classical Black-Scholes model against the Heston stochastic volatility model with a Vasicek interest rate model.
Keywords: 330; unit-linked policies; pure endowment; term insurance; stochastic volatility models; stochastic interest rates